Determination of surface tension and contact angle by the axisymmetric bubble and droplet shape analysis; Thermophysics and Aeromechanics; Vol. 22, iss. 3 - Marchuk I. V.; Cheverda V. V.; Strizhak P. A. Pavel Alexandrovich; Kabov O. A. Oleg Aleksandrovich (2015, 2015)
Title screen